2015
DOI: 10.1007/s11064-015-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Nicotinic Receptor Agonists for the Treatment of Chemotherapy-Induced Cognitive Deficits

Abstract: Over the past several decades, research in both humans and animals has established the existence of persistent cognitive deficits resulting from exposure to chemotherapeutic agents. Nevertheless, there has been very little research addressing the treatment of chemotherapy-induced cognitive deficits and there is currently no approved treatment for this condition, often referred to as 'chemo-brain.' Several drugs that enhance cholinergic function and/or increase nicotinic acetylcholine receptor (nAChR) activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 188 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…It has been suggested that receptor desensitization is a major contributor to the upregulation of nAChR subunits that is observed in chronic users of nicotine-containing products [ 154 , 157 ]. Because of the relatively conserved receptor binding sites of nAChRs for conventional agonists such as acetylcholine, [ 143 ] the subtype selectivity of allosteric modulators may be achieved easily by designing drug ligands that bind to various allosteric sites in diverse nAChR subunits [ 116 , 123 , 124 , 158 - 165 ].…”
Section: Insight From Allosteric Modulation Of Nicotinic Receptor Sigmentioning
confidence: 99%
“…It has been suggested that receptor desensitization is a major contributor to the upregulation of nAChR subunits that is observed in chronic users of nicotine-containing products [ 154 , 157 ]. Because of the relatively conserved receptor binding sites of nAChRs for conventional agonists such as acetylcholine, [ 143 ] the subtype selectivity of allosteric modulators may be achieved easily by designing drug ligands that bind to various allosteric sites in diverse nAChR subunits [ 116 , 123 , 124 , 158 - 165 ].…”
Section: Insight From Allosteric Modulation Of Nicotinic Receptor Sigmentioning
confidence: 99%
“…A meta-analysis study determined nicotine to have significant positive effects on six domains: fine motor control, alerting attention, orienting attention, short-term episodic memory, and working memory [ 39 ]. Furthermore, nicotine was reported to relieve certain attentional and cognitive deficits associated with Alzheimer’s disease, clinical symptoms of attention-deficient hyperactivity disorder, and clinical symptoms of Parkinson’s disease [ 40 ]. A systemic review demonstrated positive evidence on the effects of nicotine on attention and fine motor control in smokers, and the corresponding meta-analysis revealed a relatively small effect size (d = 0.13–0.34) for alerting and orienting attention in the smokers compared with healthy non-smokers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…All compounds, for which we revealed interactions with the muscle-type and α7 nAChRs, acted as antagonists. Finding agonists, especially selective ones, might be even more interesting, because activation of neuronal nAChRs at certain conditions can be considered as a way of treating neurological pathologies [ 32 ]. For example, α7 nAChR activator EVP-6124 shows positive results in clinical trials of treating conditions such as schizophrenia [ 33 ]; ABT-594 is a less toxic epibatidine analog with analgesic properties [ 34 ].…”
Section: Low-molecular Weight Agonists and Antagonists Of Nachrsmentioning
confidence: 99%